Changes in the upper ocean mixed layer and phytoplankton productivity along the West Antarctic Peninsula. (28th June 2018) - Schofield, Oscar; Brown, Michael; Kohut, Josh; Nardelli, Schuyler; Saba, Grace; Waite, Nicole; Ducklow, Hugh
Abstract : The West Antarctic Peninsula (WAP) has experienced significant change over the last 50 years. Using a 24 year spatial time series collected by the Palmer Long Term Ecological Research programme, we assessed long-term patterns in the sea ice, upper mixed layer depth (MLD) and phytoplankton productivity. The number of sea ice days steadily declined from the 1980s until a recent reversal that began in 2008. Results show regional differences between the northern and southern regions sampled during regional ship surveys conducted each austral summer. In the southern WAP, upper ocean MLD has shallowed by a factor of 2. Associated with the shallower mixed layer is enhanced phytoplankton carbon fixation. In the north, significant interannual variability resulted in the mixed layer showing no trended change over time and there was no significant increase in the phytoplankton productivity. Associated with the recent increases in sea ice there has been an increase in the photosynthetic efficiency (chlorophyll a -normalized carbon fixation) in the northern and southern regions of the WAP. We hypothesize the increase in sea ice results in increased micronutrient delivery to the continental shelf which in turn leads to enhanced photosynthetic performance. This article is part of the theme issue 'The marine system of the West Antarctic Peninsula: status and strategy for progress in a region of rapid change'.